Self-polymerization non-flammable electrolyte for secondary lithium-sulfur battery and preparation and lithium-sulfur secondary battery thereof

By using a mixed electrolyte of dipropylene glycol dimethyl ether and a high-boiling-point safe solvent, the flammability and polysulfide ion dissolution problems of lithium-sulfur batteries were solved, achieving high safety and long lifespan performance of lithium-sulfur batteries.

CN116779977BActive Publication Date: 2026-11-06SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210216079.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-07
Publication Date
2026-11-06
Estimated Expiration
2042-03-07

AI Technical Summary

Technical Problem

Existing lithium-sulfur batteries use carbonate and ether electrolytes that are flammable, posing a safety hazard. Furthermore, during cycling, there are issues with polysulfide ion dissolution and lithium metal consumption, affecting battery life and performance.

Method used

A self-polymerizing non-flammable electrolyte is formed by using a mixture of dipropylene glycol dimethyl ether and high-boiling-point safe solvents such as unsaturated carbonates, imidazolidinones, or flame-retardant phosphate esters as the electrolyte. This electrolyte is then combined with lithium salts and a specific ratio of solvents to prepare the positive electrode material for lithium-sulfur secondary batteries.

Benefits of technology

It improves the safety and electrochemical performance of lithium-sulfur batteries, inhibits polysulfide ion dissolution and lithium metal consumption, extends battery life, and exhibits excellent electrochemical performance and high sulfur utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116779977B_ABST
    Figure CN116779977B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of self-polymerization non-flammable electrolyte for secondary lithium-sulfur battery and its preparation, lithium-sulfur secondary battery, the electrolyte includes lithium salt and organic solvent, organic solvent selects the mixed solvent of dipropylene glycol dimethyl ether and high-boiling point safety solvent, wherein high-boiling point safety solvent includes non-flammable unsaturated carbonate, imidazolone and flame-retardant phosphate ester.Compared with prior art, the present application has non-flammability, significantly improves the safety performance of battery.In addition, dipropylene glycol dimethyl ether can occur self-polymerization reaction in the cycle process, effectively inhibit the continuous consumption of electrolyte and lithium metal;And, this characteristic shows excellent compatibility with sulfidized polyacrylonitrile positive electrode, no self-discharge, coulomb efficiency is close to 100%, has long life, high sulfur utilization and fast charging performance at room temperature and high temperature, compared with other sulfur materials and lithium metal battery has more advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of secondary lithium-sulfur battery electrolyte technology, and relates to a self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries, its preparation, and lithium-sulfur secondary batteries. Background Technology

[0002] Lithium-sulfur rechargeable batteries are rechargeable batteries that use metallic lithium as the negative electrode and sulfur-containing materials (including elemental sulfur, sulfur-based composite materials, or organic sulfides) as the positive electrode. They have high energy density (theoretical capacity density of 1672 mAh g⁻¹). -1 With advantages such as long cycle life and low cost (due to the low price of elemental sulfur), it is the development direction of the next generation of batteries.

[0003] Based on our previous research (Energy Storage Mater. 15 (2018) 299-307), Li / S@pPAN batteries exhibit good cycling performance in carbonate electrolyte systems, such as 1M LiPF6 / EC+DMC (1:1, v / v), but their electrochemical performance still needs improvement. This is mainly attributed to the severe interfacial side reactions between the carbonate solvent and the lithium metal anode, which lead to continuously increasing polarization and rapid capacity decay. Ether electrolyte systems, such as 1M LiTFSI / DOL+DME (1:1, v / v), have better compatibility with lithium metal anodes, but when matched with S@pPAN cathodes, the dissolution and shuttle of polysulfide ions occur, resulting in loss of active material and rapid capacity decay. Furthermore, both the carbonate and ether solvents mentioned above are low-boiling-point and flammable, posing safety hazards.

[0004] Dipropylene glycol dimethyl ether (DPGDME), as a safe, pollution-free, and non-flammable green solvent, was reported in 2016 as a co-solvent for magnesium-ion battery electrolytes (Electrochimica Acta 219(2016)267-276). Subsequently, it was reported as a primary solvent for lithium-disulfide battery electrolytes in 2017 and 2019 (J. Electrochemical Soc. 164(2017)A897-A901; ACS Sustainable Chem. Eng. 7(2019)5209-5222). However, using DPGDME as the sole electrolyte solvent in lithium-sulfur batteries still presents the problem of polysulfide ion dissolution and shuttle; furthermore, due to interfacial side reactions, the liquid solvent and the negative electrode lithium source are irreversibly consumed until depleted during cycling, limiting the battery's cycle life. This invention is based on these issues. Summary of the Invention

[0005] The purpose of this invention is to provide a self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries and its preparation, as well as lithium-sulfur secondary batteries, to improve battery life, etc.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] One of the technical solutions of the present invention provides a self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries, comprising lithium salt and organic solvent. The organic solvent is selected as a mixed solvent composed of dipropylene glycol dimethyl ether (DPGDME) and a high-boiling-point safe solvent. The high-boiling-point safe solvent includes one or a combination of several of the following: non-flammable unsaturated carbonates, imidazolides, or flame-retardant phosphate esters.

[0008] Furthermore, the unsaturated carbonate is selected from one or a combination of two of ethylene ethylene carbonate (VEC) and ethylene ethylene carbonate (VC).

[0009] Furthermore, the imidazolinones are selected from at least one of 1,3-dimethyl-2-imidazolinone (DMI), 1-methyl-2-imidazolinone (MMI), and 2-imidazolidinone (MI).

[0010] Furthermore, the phosphate ester is selected from one or more of trimethyl phosphate (TMP), triethyl phosphate (TEP), dimethyl methyl phosphate (DMMP), trimethyl phosphite (TMPi), and triethyl phosphite (TEPi).

[0011] Furthermore, in the mixed solvent, the volume ratio of dipropylene glycol dimethyl ether to the high-boiling-point safe solvent is 1:0.05–20. Even further, the volume ratio of dipropylene glycol dimethyl ether to the high-boiling-point safe solvent is 1:0.1–1. Excessive dipropylene glycol dimethyl ether content will reduce the ionic conductivity of the electrolyte; excessive unsaturated carbonate and imidazolidinone content will increase the electrolyte viscosity and form a thicker interface layer at the lithium anode, which is detrimental to long-term cycle stability; excessive phosphate ester content will worsen the compatibility with the sulfur cathode.

[0012] Furthermore, the lithium salt is selected from one or more of lithium nitrate (LiNO3), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonate)imide (LiTFSI), and lithium bis(fluorosulfonylimide) (LiFSI).

[0013] Furthermore, the concentration of lithium salt in the electrolyte is 0.5-2 mol·L⁻¹. -1 .

[0014] The second technical solution of the present invention provides a method for preparing a self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries. Lithium salt is added to an organic solvent and completely dissolved to obtain the target product, an intrinsically safe electrolyte for secondary lithium-sulfur batteries.

[0015] The third technical solution of the present invention provides a secondary lithium-sulfur battery containing a self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries as described in any of the above-mentioned embodiments.

[0016] Meanwhile, the preparation method of the positive electrode of the lithium-sulfur secondary battery of the present invention includes the following steps: uniformly dispersing sulfur-containing material, binder, and conductive agent in water at a mass ratio of (60-80):(2-20):(4-40), then coating the mixture onto a current collector, drying it, and pressing it into a sheet to obtain the positive electrode of the lithium-sulfur secondary battery. The sulfur-containing material is elemental sulfur (S8) or lithium polysulfide (Li2S). n (where 1≤n≤8), sulfur-based composite materials, organic sulfur compounds or carbon-sulfur polymers (C2S) x ) n (Where x is 2-20, and n≥2); the sulfur-based composite material is obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 4-16:1, heating to 250-400℃ under nitrogen protection, and holding at that temperature for 1-16 hours. The molecular weight of the polyacrylonitrile is 10,000-1,000,000. The conductive agent is acetylene black or conductive graphite. The current collector is aluminum foil, aluminum mesh, carbon-coated aluminum foil, carbon-coated aluminum mesh, nickel mesh, or nickel foam. The binder is carbonyl-β-cyclodextrin, polyvinylidene fluoride (PVDF), sodium alginate, carboxymethyl cellulose (CMC), carboxylated styrene-butadiene rubber (SCR), guar gum (GG), or polyacrylic acid (PAA).

[0017] The dipropylene glycol dimethyl ether, unsaturated carbonates, and imidazolides used in this invention exhibit high boiling points and non-flammability, while phosphate esters exhibit high boiling points and flame retardancy, significantly improving battery safety. Simultaneously, solvents such as ethylene ethylene carbonate form a protective interface layer on the positive electrode surface during initial cycling, inhibiting the dissolution and shuttle of polysulfide ions. Furthermore, during subsequent cycles, dipropylene glycol dimethyl ether and ethylene ethylene carbonate gradually undergo self-polymerization, further suppressing the shuttle effect and effectively inhibiting the continuous consumption of electrolyte and lithium metal, thereby increasing battery life. Lithium-sulfurized polyacrylonitrile batteries using this electrolyte exhibit excellent electrochemical performance, with no self-discharge, an average coulombic efficiency of nearly 100%, and long lifespan, high sulfur utilization, and fast-charging performance at both room and high temperatures.

[0018] Compared with existing technologies, the electrolyte of this invention significantly improves the safety and electrochemical performance of secondary lithium-sulfur batteries, especially at high temperatures, achieving a synergistic improvement in both safety and electrochemical performance. The dipropylene glycol dimethyl ether and high-boiling-point ester solvents make the electrolyte completely non-flammable. Its self-polymerization reaction ensures long-term stable cycling of the lithium anode and exhibits excellent compatibility with the S@pPAN cathode. It has no self-discharge, achieves an average coulombic efficiency of 100% at high rate cycling, and has high sulfur utilization. Attached Figure Description

[0019] Figure 1 This refers to the combustion (non-flammable) of the electrolyte when dipropylene glycol dimethyl ether, ethylene carbonate, and a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio of 2:1) are used.

[0020] Figure 2 This refers to the combustion (non-flammable) of the electrolyte when a mixed solvent of dipropylene glycol dimethyl ether and 1,3-dimethyl-2-imidazolinone (volume ratio 9:1) is used in Example 2.

[0021] Figure 3 This refers to the combustion (non-flammable) of the electrolyte when a mixed solvent of dipropylene glycol dimethyl ether and triethyl phosphate (volume ratio 1:1) is used in Example 3.

[0022] Figure 4 This is the lithium symmetric deposition and dissolution curve of the dipropylene glycol dimethyl ether-based electrolyte obtained in Example 4 at room temperature. The test temperature was 25°C and the current density was 1 mA cm⁻¹. -2 The surface capacity is 1mAh cm -2 .

[0023] Figure 5 It is the relative molecular mass of the dipropylene glycol dimethyl ether electrolyte obtained in Example 4 after 750 hours of cycling at room temperature.

[0024] Figure 6 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 5 using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1) at room temperature. The test temperature was 25°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 1mAh cm -2 .

[0025] Figure 7 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 5 using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1) at high temperature. The test temperature was 50°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 1mAh cm -2 .

[0026] Figure 8 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 5 using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1) at high temperature. The test temperature was 50°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 10mAh cm -2 .

[0027] Figure 9 The lithium deposition morphology obtained in Example 5 is shown after 300 hours of cycling in a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1) at high temperature. The test temperature was 50°C and the current density was 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 .

[0028] Figure 10 The images show the reflectance infrared spectra of the electrolyte before and after 300 hours of cycling at room temperature and high temperature, respectively, with the mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio of 2:1) obtained in Example 5, as well as comparisons with pure dipropylene glycol dimethyl ether solvent and ethylene carbonate solvent.

[0029] Figure 11 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 6 using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 9:1) at room temperature. The test temperature was 25°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 1mAh cm -2 .

[0030] Figure 12 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 6 using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 9:1) at room temperature. The test temperature was 50°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 1mAh cm -2 .

[0031] Figure 13 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 6 using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 9:1) at room temperature. The test temperature was 50°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 10mAh cm -2 .

[0032] Figure 14The table shows the room temperature cycling performance curves of a lithium-sulfur secondary battery in an electrolyte solution obtained in Example 7, using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratios of 2:1 and 9:1, respectively), with a sulfur content of 49%, compared with the room temperature performance of a lithium-sulfur secondary battery using a standard electrolyte (STD).

[0033] Figure 15 The self-discharge performance of a lithium-sulfur secondary battery under full charge was tested in the electrolyte obtained in Example 8, which was a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1) at room temperature.

[0034] Figure 16 The self-discharge performance of a lithium-sulfur secondary battery under different voltage conditions was tested in the electrolyte obtained in Example 8, which was a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1).

[0035] Figure 17 The high-temperature cycling performance curve of the lithium-sulfur secondary battery in the electrolyte obtained in Example 9, which is a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1).

[0036] Figure 18 The high-temperature cycling performance curve of a lithium-sulfur secondary battery under high-rate conditions is obtained in Example 9 using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1).

[0037] Figure 19 The rate performance curve of the lithium-sulfur secondary battery in the electrolyte obtained in Example 9, which is a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio of 2:1).

[0038] Figure 20 The performance curves are obtained in Example 9 under high-rate fast charging conditions in an electrolyte solution containing a mixture of dipropylene glycol dimethyl ether and ethylene carbonate in a volume ratio of 2:1.

[0039] Figure 21 The coulombic efficiency of a lithium-sulfur secondary battery under different test procedures was tested in the electrolyte obtained in Example 9, which was a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1) at high temperature.

[0040] Figure 22 The self-discharge performance of a lithium-sulfur secondary battery under different voltage conditions was tested in the electrolyte obtained in Example 9, which was a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1).

[0041] Figure 23This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 10 at room temperature using a mixed solvent of dipropylene glycol dimethyl ether and vinylene carbonate (volume ratio 2:1). The test temperature was 25°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 1mAh cm -2 .

[0042] Figure 24 The figure shows the room temperature cycling performance curve of a lithium-sulfur secondary battery in the electrolyte obtained in Example 11, which is a mixed solvent of dipropylene glycol dimethyl ether and vinylene carbonate (volume ratio 2:1). The sulfur content is 49%.

[0043] Figure 25 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 12 at room temperature using a mixed solvent of dipropylene glycol dimethyl ether and 1,3-dimethyl-2-imidazolinone (volume ratio 9:1). The test temperature was 50°C and the current density was 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 .

[0044] Figure 26 The figure shows the room temperature cycling performance curve of a lithium-sulfur secondary battery in the electrolyte obtained in Example 13, which is a mixed solvent of dipropylene glycol dimethyl ether and 1,3-dimethyl-2-imidazolinone (volume ratio 9:1). The sulfur content is 49%.

[0045] Figure 27 This is the lithium symmetric deposition and dissolution curve of the electrolyte obtained in Example 14 using a mixed solvent of dipropylene glycol dimethyl ether and triethyl phosphate (volume ratio 1:1) at room temperature. The test temperature was 25°C and the current density was 0.5 mA cm⁻¹. -2 The surface capacity is 0.5mAh cm -2 .

[0046] Figure 28 The figure shows the room temperature cycling performance curve of a lithium-sulfur secondary battery in the electrolyte obtained in Example 15, which is a mixed solvent of dipropylene glycol dimethyl ether and triethyl phosphate (volume ratio 1:1). The sulfur content is 49%. Detailed Implementation

[0047] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0048] In the following embodiments, unless otherwise specified, the raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0049] Example 1

[0050] Dipropylene glycol dimethyl ether and ethylene ethylene carbonate were uniformly mixed in a glove box at a certain volume ratio and stirred until homogeneous. The volume ratio of the two solvents was 2:1. LiFSI was then added to this mixed solvent to obtain a 1M LiFSI / 2D1V electrolyte (i.e., the concentration of LiFSI in the electrolyte was 1 mol / L, the same below). Combustion tests showed that... Figure 1 The two solvents used and the electrolyte prepared are non-flammable.

[0051] Example 2

[0052] Dipropylene glycol dimethyl ether and 1,3-dimethyl-2-imidazolinone were uniformly mixed in a glove box at a certain volume ratio and stirred until homogeneous. The volume ratio of the two solvents was 9:1. LiFSI was then added to this mixed solvent to obtain a 1M LiFSI / 9D1DMI electrolyte. Combustion tests showed that... Figure 2 The electrolyte used in this preparation does not burn.

[0053] Example 3

[0054] Dipropylene glycol dimethyl ether and triethyl phosphate were uniformly mixed in a glove box at a certain volume ratio and stirred until homogeneous. The volume ratio of the two solvents was 1:1. LiFSI was then added to this mixed solvent to obtain a 1M LiFSI / 1D1T electrolyte. Combustion tests showed that... Figure 3 The electrolyte used is non-combustible.

[0055] Example 4

[0056] LiFSI was added to dipropylene glycol dimethyl ether solvent to obtain a 1.8 M LiFSI / DPGDME electrolyte. A lithium-ion symmetric coin cell was constructed using 1.8 M LiFSI / DPGDME as the electrolyte and a 25 μm thick Celgard porous polyethylene membrane as the separator.

[0057] Deposition / stripping cycles were performed at 25°C with a current density of 1 mA cm⁻¹. -2 The surface capacity is 1mAh cm -2 ,like Figure 4 As shown, the symmetrical cell maintained a stable voltage curve over 2600 hours. Meanwhile, the voltage-time and voltage-capacity curves changed, indicating that the electrolyte underwent a self-polymerization reaction during cycling.

[0058] The relative molecular mass of the electrolyte after cycling was measured by gel permeation chromatography, such as... Figure 5 As shown, the weight-average molecular weight (Mw) is 3350 g mol. -1 This indicates that the DPGDME solvent undergoes self-polymerization during the cycling process.

[0059] Example 5

[0060] A lithium-ion symmetrical coin cell was constructed using 1M LiFSI / 2D1V as the electrolyte and a 25-micron-thick Celgard porous polyethylene membrane as the separator.

[0061] Deposition / stripping cycles were performed at 25°C with a current density of 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 ,like Figure 6 As shown, the symmetrical cell maintained a stable voltage curve over 3000 hours. Meanwhile, the voltage-time and voltage-capacity curves changed, indicating that the electrolyte underwent a self-polymerization reaction during cycling.

[0062] Deposition / stripping cycles were performed at 50°C with a current density of 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 ,like Figure 7 As shown, the symmetrical battery maintained a stable voltage curve over 800 hours. The areal capacity was further increased to 10 mAh / cm². -2 ,like Figure 8 As shown, the symmetrical cell maintains a stable voltage curve over 1000 hours.

[0063] Figure 9 The image shows the lithium deposition morphology after 300 hours of symmetric cell cycling at 50°C. As can be seen, the deposition morphology includes a polymer outer layer and a dense, salt-dominated SEI inner layer. LiFSI reduction and decomposition constructed the dense, bulk lithium deposition in the inner layer. The polymer outer layer originates from solvent molecules undergoing self-polymerization, primarily composed of polyethers.

[0064] Figure 10 The images show the reflectance infrared spectra of the electrolyte obtained in Example 2 before and after cycling at room temperature and high temperature for 300 hours, using a mixed solvent of dipropylene glycol dimethyl ether and ethylene carbonate (volume ratio 2:1). These spectra are compared with those of pure dipropylene glycol dimethyl ether solvent and pure ethylene carbonate solvent. Compared to before cycling, the number of aliphatic chain CH stretching peaks in dipropylene glycol dimethyl ether decreased after cycling, indicating that it underwent self-polymerization during the cycling process. Simultaneously, the double bond characteristic peaks of ethylene carbonate disappeared after cycling, indicating that it also underwent self-polymerization during the cycling process.

[0065] Example 6

[0066] Dipropylene glycol dimethyl ether and ethylene ethylene carbonate were uniformly mixed in a glove box at a specific volume ratio and stirred until homogeneous. The volume ratio of the two solvents was 9:1. LiFSI was then added to the mixed solvent to obtain a 1M LiFSI / 9D1V electrolyte. Using 1M LiFSI / 9D1V as the electrolyte and a 25-micron-thick Celgard porous polyethylene membrane as the separator, a lithium-ion symmetric coin cell was constructed.

[0067] Deposition / stripping cycles were performed at 25°C with a current density of 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 ,like Figure 11 As shown, the symmetrical cell maintains a stable voltage curve over 1600 hours.

[0068] Deposition / stripping cycles were performed at 50°C with a current density of 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 ,like Figure 12 As shown, the symmetrical cell maintained a stable voltage curve over 1000 hours. The areal capacity was further increased to 10 mAh / cm². -2 ,like Figure 13 As shown, the symmetrical cell maintains a stable voltage curve over 1000 hours.

[0069] Example 7

[0070] Sulfur-based composite material, carboxylated styrene-butadiene rubber, guar gum, and Super P were uniformly and gently dispersed in deionized water at a mass ratio of 80:5:5:10. The mixture was then uniformly coated onto carbon-coated aluminum foil, dried, and pressed into sheets to obtain the positive electrode of a lithium-sulfur secondary battery. The sulfur-based composite material was obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 8:1, heating to 300°C under nitrogen protection, and holding at that temperature for 6 hours to obtain a sulfur composite material with a sulfur content of 49%.

[0071] Battery assembly and testing were conducted as follows: a 1M LiPF6 / EC+DMC (1:1, v / v) electrolyte was prepared as the standard electrolyte (STD). Lithium-sulfur secondary batteries were assembled using lithium metal as the negative electrode, with a 25-micron-thick Celgard porous polyethylene membrane as the separator. The electrolytes used were STD, 1M LiFSI / 2D1V, and 1M LiFSI / 9D1V.

[0072] The charge / discharge cutoff voltage is 1-3V (vs. Li / Li). + The test ratio was 0.2C, and the sulfur loading was 1.5 mg / cm³. -2 The test temperature is 25℃, such as Figure 14 As shown, the capacity of lithium-sulfur secondary batteries using standard electrolytes decays rapidly.

[0073] After 100 cycles, the capacity retention rate was only 69.9%. This is because the carbonate electrolyte has poor compatibility with the lithium anode, and continuous interfacial side reactions lead to the continuous thickening of the interfacial side reaction layer, increasing battery polarization and thus rapidly reducing capacity. In contrast, the lithium-sulfur secondary battery using 1M LiFSI / 9D1V showed significantly improved cycle stability, with a capacity retention rate of 94.0% after 100 cycles. The lithium-sulfur secondary battery using 1M LiFSI / 2D1V exhibited the best cycle stability, with a capacity retention rate of 99.9% after 100 cycles and virtually no capacity loss.

[0074] The superior electrochemical performance of lithium-sulfur secondary batteries is due to the following reasons: In the initial cycle, ethylene ethylene carbonate can form a protective carbonate-containing interface layer on the surface of the sulfurized polyacrylonitrile cathode, thereby inhibiting the dissolution and shuttle of polysulfide ions; In subsequent cycles, dipropylene glycol dimethyl ether and ethylene ethylene carbonate gradually undergo self-polymerization reactions, which can effectively inhibit the continuous consumption of electrolyte and lithium metal, thereby increasing battery life; Furthermore, the formation of a polyether layer with high ionic conductivity can effectively reduce battery polarization and improve the coulombic efficiency of the cathode.

[0075] Example 8

[0076] Sulfur-based composite material, carboxylated styrene-butadiene rubber, guar gum, and Super P were uniformly and gently dispersed in deionized water at a mass ratio of 80:5:5:10. The mixture was then uniformly coated onto carbon-coated aluminum foil, dried, and pressed into sheets to obtain the positive electrode of a lithium-sulfur secondary battery. The sulfur-based composite material was obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 8:1, heating to 300°C under nitrogen protection, and holding at that temperature for 6 hours to obtain a sulfur composite material with a sulfur content of 49%.

[0077] The battery assembly and testing were as follows: a lithium-sulfur secondary battery was assembled using lithium metal as the negative electrode, with a 25-micron thick Celgard porous polyethylene membrane as the separator, and the electrolyte was 1M LiFSI / 2D1V.

[0078] The charge / discharge cutoff voltage is 1-3V (vs. Li / Li). + The test ratio was 1C, and the sulfur loading was 1.5 mg / cm³. -2 The test temperature was 25℃. After battery activation, a self-discharge test was conducted at full charge (3V). Figure 15 As shown, after 720 hours of rest, the lithium-sulfur secondary battery showed no capacity decay during continuous operation. Furthermore, self-discharge experiments were conducted under different voltage conditions, such as... Figure 16 As shown, after being left to stand for 48 hours, the lithium-sulfur secondary battery that was subsequently put into operation showed no capacity decay.

[0079] Example 9

[0080] Sulfur-based composite material, carboxylated styrene-butadiene rubber, guar gum, and Super P were uniformly and gently dispersed in deionized water at a mass ratio of 80:5:5:10. The mixture was then uniformly coated onto carbon-coated aluminum foil, dried, and pressed into sheets to obtain the positive electrode of a lithium-sulfur secondary battery. The sulfur-based composite material was obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 8:1, heating to 300°C under nitrogen protection, and holding at that temperature for 6 hours to obtain a sulfur composite material with a sulfur content of 49%.

[0081] The battery assembly and testing were as follows: a lithium-sulfur secondary battery was assembled using lithium metal as the negative electrode, with a 25-micron thick Celgard porous polyethylene membrane as the separator, and the electrolyte was 1M LiFSI / 2D1V.

[0082] The charge / discharge cutoff voltage is 1-3V (vs. Li / Li). + The sulfur loading is 1.5 mg / cm³. -2 The test temperature was 50℃. For example... Figure 17 As shown, after 100 cycles at 1C, the capacity retention was 97.9%, and the specific capacity of the composite material was 770.0 mAh g. -1 This corresponds to a sulfur utilization rate of 94.0% and an average coulombic efficiency of 99.94%. Figure 18 The cycling stability of a 1M LiFSI / 2D 1V lithium-sulfur secondary battery under high-rate conditions was demonstrated. After 250 cycles at 4C, the specific capacity of the composite material remained at 762.3 mAh g⁻¹. -1 .

[0083] Figure 19 The rate performance of a lithium-sulfur secondary battery using 1M LiFSI / 2D1V was demonstrated. With a constant discharge rate, increasing the charge rate resulted in virtually no capacity decay, indicating excellent fast-charging performance. Figure 20 This demonstrates that even with 10C ultra-high-rate fast charging, the battery still exhibits excellent cycle stability. Further testing of the coulombic efficiency of the lithium-sulfur secondary battery under different charge-discharge programs, such as... Figure 21 As shown, in the low-rate discharge (0.5C) and high-rate charge (2C) modes, the average coulombic efficiency is as high as 99.9997%.

[0084] Furthermore, self-discharge experiments were conducted under different voltage conditions at a test temperature of 50℃. Figure 22 As shown, after being left to stand for 48 hours, the lithium-sulfur secondary battery that was subsequently put into operation showed no capacity decay.

[0085] Example 10

[0086] Dipropylene glycol dimethyl ether and vinylene carbonate were uniformly mixed in a glove box at a certain volume ratio and stirred until homogeneous. The volume ratio of the two solvents was 2:1. LiFSI was then added to the mixed solvent to obtain a 1M LiFSI / 2D1VC electrolyte. Using 1M LiFSI / 2D1VC as the electrolyte and a 25-micron-thick Celgard porous polyethylene membrane as the separator, a lithium-ion symmetric coin cell was constructed.

[0087] Deposition / stripping cycles were performed at 25°C with a current density of 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 ,like Figure 23 As shown, the voltage curve of the symmetrical cell remains stable over 90 hours.

[0088] Example 11

[0089] Sulfur-based composite material, carboxylated styrene-butadiene rubber, guar gum, and Super P were uniformly and gently dispersed in deionized water at a mass ratio of 80:5:5:10. The mixture was then uniformly coated onto carbon-coated aluminum foil, dried, and pressed into sheets to obtain the positive electrode of a lithium-sulfur secondary battery. The sulfur-based composite material was obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 8:1, heating to 300°C under nitrogen protection, and holding at that temperature for 6 hours to obtain a sulfur composite material with a sulfur content of 49%.

[0090] The battery assembly and testing were as follows: lithium metal was used as the negative electrode to assemble a lithium-sulfur secondary battery, a 25-micron thick Celgard porous polyethylene membrane was used as the separator, and the electrolyte was 1M LiFSI / 2D1VC.

[0091] The charge / discharge cutoff voltage is 1-3V (vs. Li / Li). + The test ratio was 0.2C, and the sulfur loading was 1.5 mg / cm³. -2 The test temperature is 25℃, such as Figure 24 As shown.

[0092] Example 12

[0093] Dipropylene glycol dimethyl ether and 1,3-dimethyl-2-imidazolinone were uniformly mixed in a glove box at a specific volume ratio and stirred until homogeneous. The volume ratio of the two solvents was 9:1. LiFSI was then added to the mixed solvent to obtain a 1M LiFSI / 9D1DMI electrolyte. Using 1M LiFSI / 9D1DMI as the electrolyte and a 25-micron-thick Celgard porous polyethylene membrane as the separator, a lithium-ion symmetric coin cell was constructed.

[0094] Deposition / stripping cycles were performed at 50°C with a current density of 0.5 mA / cm². -2 The surface capacity is 1mAh cm -2 ,like Figure 25As shown, the symmetrical cell maintains a stable voltage curve over 1800 hours.

[0095] Example 13

[0096] Sulfur-based composite material, carboxylated styrene-butadiene rubber, guar gum, and Super P were uniformly and gently dispersed in deionized water at a mass ratio of 80:5:5:10. The mixture was then uniformly coated onto carbon-coated aluminum foil, dried, and pressed into sheets to obtain the positive electrode of a lithium-sulfur secondary battery. The sulfur-based composite material was obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 8:1, heating to 300°C under nitrogen protection, and holding at that temperature for 6 hours to obtain a sulfur composite material with a sulfur content of 49%.

[0097] The battery assembly and testing were as follows: lithium metal was used as the negative electrode to assemble a lithium-sulfur secondary battery, a 25-micron thick Celgard porous polyethylene membrane was used as the separator, and the electrolyte was 1M LiFSI / 9D1DMI.

[0098] The charge / discharge cutoff voltage is 1-3V (vs. Li / Li). + The test ratio was 0.2C, and the sulfur loading was 1.5 mg / cm³. -2 The test temperature is 50℃, such as Figure 26 As shown, it exhibits excellent cycle stability.

[0099] Example 14

[0100] Dipropylene glycol dimethyl ether and triethyl phosphate were uniformly mixed in a glove box at a certain volume ratio and stirred until homogeneous. The volume ratio of the two solvents was 1:1. LiFSI was then added to the mixed solvent to obtain a 1M LiFSI / 1D1T electrolyte. Using 1M LiFSI / 1D1T as the electrolyte and a 25-micron-thick Celgard porous polyethylene membrane as the separator, a lithium-ion symmetric coin cell was constructed.

[0101] Deposition / stripping cycles were performed at 25°C with a current density of 0.5 mA / cm². -2 The surface capacity is 0.5mAh cm -2 ,like Figure 27 As shown, the voltage curve of the symmetrical cell remained stable over 500 hours.

[0102] Example 15

[0103] Sulfur-based composite material, carboxylated styrene-butadiene rubber, guar gum, and Super P were uniformly and gently dispersed in deionized water at a mass ratio of 80:5:5:10. The mixture was then uniformly coated onto carbon-coated aluminum foil, dried, and pressed into sheets to obtain the positive electrode of a lithium-sulfur secondary battery. The sulfur-based composite material was obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 8:1, heating to 300°C under nitrogen protection, and holding at that temperature for 6 hours to obtain a sulfur composite material with a sulfur content of 49%.

[0104] The battery assembly and testing were as follows: lithium metal was used as the negative electrode to assemble a lithium-sulfur secondary battery, a 25-micron thick Celgard porous polyethylene membrane was used as the separator, and the electrolyte was 1M LiFSI / 1D1T.

[0105] The charge / discharge cutoff voltage is 1-3V (vs. Li / Li). + The test ratio was 0.2C, and the sulfur loading was 1.5 mg / cm³. -2 The test temperature is 25℃, such as Figure 28 As shown, it exhibits excellent cycle stability.

[0106] Example 16

[0107] This embodiment is basically the same as that of Embodiment 12, except that in this embodiment, the phosphate ester solvent in the mixed solvent is 1-methyl-2-imidazolinone (MMI).

[0108] Example 17

[0109] This embodiment is basically the same as that of embodiment 12, except that in this embodiment, the phosphate ester solvent in the mixed solvent is trimethyl phosphate (MI).

[0110] Example 18

[0111] This embodiment is basically the same as that of embodiment 14, except that in this embodiment, the phosphate ester solvent in the mixed solvent is 2-imidazolidineone TMP.

[0112] Example 19

[0113] This embodiment is basically the same as embodiment 14, except that in this embodiment, the phosphate ester solvent in the mixed solvent is trimethyl phosphite (TMPi).

[0114] Example 20

[0115] This embodiment is basically the same as embodiment 14, except that in this embodiment, the phosphate ester solvent in the mixed solvent is triethyl phosphite (TEPi).

[0116] Example 21

[0117] This embodiment is basically the same as that of embodiment 14, except that in this embodiment, the phosphate ester solvent in the mixed solvent is dimethyl methyl phosphate (DMMP).

[0118] Example 22

[0119] This embodiment is basically the same as embodiment 7. This embodiment contains a lithium-sulfur secondary battery with a self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries. The preparation method of its positive electrode includes the following steps: uniformly dispersing sulfur-containing materials, binders, and conductive agents in water, then coating them on a current collector, drying them, and pressing them into sheets to obtain the positive electrode of the lithium-sulfur secondary battery.

[0120] The mass ratio of sulfur-containing materials, binders, and conductive agents can be selected within the range of 60-80:2-20:4-40 (e.g., 60:20:4, 70:10:20, 80:2:40, etc.); the sulfur-containing materials can be elemental sulfur (S8) or lithium polysulfide (Li2S). n (where 1≤n≤8), sulfur-based composite materials, organic sulfur compounds or carbon-sulfur polymers (C2S) x ) n (Where x is 2-20 and n≥2), choose according to the situation; the sulfur-based composite material is obtained by mixing elemental sulfur and polyacrylonitrile at a mass ratio of 4-16:1, heating to 250-400℃ under nitrogen protection and holding for 1-16 hours. The molecular weight of polyacrylonitrile is 10,000-1,000,000. The conductive agent can be acetylene black or conductive graphite, choose according to the situation. The current collector can be aluminum foil, aluminum mesh, carbon-coated aluminum foil, carbon-coated aluminum mesh, nickel mesh or nickel foam, choose according to the situation. The binder can be carbonyl-β-cyclodextrin, polyvinylidene fluoride (PVDF), sodium alginate, carboxymethyl cellulose (CMC), guar gum (GG) or polyacrylic acid (PAA), choose according to the situation.

[0121] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries, characterized in that, It includes lithium salt and organic solvent, wherein the organic solvent is selected as a mixed solvent composed of dipropylene glycol dimethyl ether and a high-boiling-point safe solvent, wherein the high-boiling-point safe solvent is ethylene carbonate; The volume ratio of dipropylene glycol dimethyl ether to a high-boiling-point safe solvent is 1:0.1~1.

2. The self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries according to claim 1, characterized in that, The lithium salt is selected from one or more of lithium nitrate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonate)imide, and lithium bis(fluorosulfonylimide).

3. The self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries according to claim 1, characterized in that, The concentration of lithium salt in the electrolyte is 0.5-2 mol·L⁻¹ -1 .

4. A method for preparing a self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries as described in any one of claims 1-3, characterized in that, Lithium salt is added to an organic solvent and completely dissolved to obtain the target product, an intrinsically safe electrolyte for secondary lithium-sulfur batteries.

5. A secondary lithium-sulfur battery comprising the self-polymerizing non-flammable electrolyte for secondary lithium-sulfur batteries as described in any one of claims 1-3.

Citation Information

Patent Citations

  • Intrinsic safety electrolyte for secondary lithium-sulfur battery and preparation method thereof

    CN109599592A

  • Lithium-sulfur secondary battery with long cycle life and 100% coulomb efficiency

    CN110611084A